2022
DOI: 10.1007/s00540-022-03036-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and mortality among survivors of acute respiratory distress syndrome in South Korea: a nationwide cohort study

Abstract: Purpose Worsening quality of life (QOL) is an important health issue in acute respiratory distress syndrome (ARDS) survivors. We aimed to investigate the prevalence of worsening QOL among ARDS survivors and their association with mortality. Methods South Korean National Health Insurance database information for all adults admitted to intensive care units for ARDS from January 1, 2010 to December 31, 2018 who survived ≥ 365 days were included in this study. Results A total of 4452 ARDS survivors were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For example, a previous study reported that the median value of total hospitalization cost was USD 2,555.6 (IQR: 1,335.2-5,757.4) among patients with sepsis in South Korea in 2005-2012 (18). Moreover, we reported recently that the mean expense of hospitalization among survivors of ARDS was USD 9,714.1 (standard deviation: 12,266.7) in South Korea (19). Therefore, the differences in ECMO support cost should be interpreted and compared carefully with previous studies (8)(9)(10), considering the unique feature of the South Korean NHIS system.…”
Section: Discussionmentioning
confidence: 82%
“…For example, a previous study reported that the median value of total hospitalization cost was USD 2,555.6 (IQR: 1,335.2-5,757.4) among patients with sepsis in South Korea in 2005-2012 (18). Moreover, we reported recently that the mean expense of hospitalization among survivors of ARDS was USD 9,714.1 (standard deviation: 12,266.7) in South Korea (19). Therefore, the differences in ECMO support cost should be interpreted and compared carefully with previous studies (8)(9)(10), considering the unique feature of the South Korean NHIS system.…”
Section: Discussionmentioning
confidence: 82%
“…The types of disability included physical, brain lesions, visual, hearing, speech, intellectual, mental, renal, heart, respiratory, hepatopathy, intestinal and urinary stulae, and epilepsy. Each disability was rigorously classi ed according to legal standards by specialist physicians in each respective eld, with a grading system ranging from 1 to 6 33 . Grades 1 through 3 were considered severe disabilities, while grades 4 through 6 were categorized as mild to moderate disabilities, respectively.…”
Section: Data Collection and De Nitionsmentioning
confidence: 99%
“…Due to the diverse causes and complex pathogenesis, ARDS treatment is also unspecific, poorly described, and considered an important unmet medical need [ 7 , 8 ]. In addition to the high rates of morbidity and mortality, ARDS has a great impact on the quality of life of patients requiring a better understanding of their pathogenesis and new treatment options [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%